Peningkatan Aktivitas dan Hasil Belajar Siswa melalui Penerapan Model Discovery Learning Berbantuan TTS - Nabilatu Rahmi; Ardi Ardi; Asrul Asrul; Wirdati Wirdati; Lufri Lufri; Fitri Olivia Rahma (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The low level of student learning activity negatively impacts learning outcomes, often falling below the KKTP standard. To enhance both learning activities and results, the discovery learning model supported by CWP was implemented. This study employed Classroom Action Research, utilizing observation sheets, learning outcome assessments, field notes, and documentation as research instruments. Data on learning activities were gathered through observation and analyzed by calculating the percentage of each activity. Learning outcomes were assessed descriptively to determine students' average performance and the percentage of students achieving classical learning completeness. Research findings indicate that student learning activity percentages improved across cycles: cycle I recorded 28.48%, while cycle II increased to 51.36%. Similarly, average learning outcomes progressed, with pre-cycle scores at 70.53, cycle I at 71.56, and cycle II at 82.18. These results demonstrate that implementing the discovery learning model with CWP support can effectively enhance learning activities and positively influence student performance.